WHILE WE'RE AT IT. - Neuhaus, Richard John (First Things: A Monthly Journal of Religion & Public Life, 1992)
Presents updates related to religion as of October 1992. Decision of publication company Doubleday to reissue the classic works of author John Henry Newman; Plan of the members of the Millennium Society to travel to Egypt aboard the Queen Elizabeth II cruise liner to celebrate the year 2000 at the Great Pyramid of Cheops; Information on the film "Marketplace Prophets."